Socio-economic Impact of Science and Technology on Society: An Analytical Study - Dr. Manoj Gupta & Dr. Seema Yadav (International journal of economic perspectives, 2022)
As we all know that society needs to see science not as a luxury of funding but as a fundamental activity that drives enlightenment, economics and society. It is hard to imagine our life now without science and technology. The discovery of new plants and the establishment of satellites in space is because of the very same science and technology. Similarly, science and technology have also made an impact on the medical and agricultural fields. Moreover, technology has enhanced the production of different crops and technological advancement of our country have enhanced the Indian economy.